Fatal attraction? Access to early retirement and mortality - Andreas Kuhn; Jean-Philippe Wuellrich; Josef Zweimüller (Institute for the Study of Labor (IZA), 2010)
We estimate the causal effect of early retirement on mortality for blue-collar workers. To overcome the problem of endogenous selection, we exploit an exogenous change in unemployment insurance rules in Austria that allowed workers in eligible regions to withdraw from the workforce up to 3.5 years earlier than those in non-eligible regions. For males, instrumental-variable estimates show a significant 2.4 percentage points (about 13%) increase in the probability of dying before age 67. We do not find any adverse effect of early retirement on mortality for females. Death causes indicate a significantly higher incidence ofcardiovascular disorders among eligible workers, suggesting that changes in health-related behavior explain increased mortality among male early retirees.
Keywords: I1; J14; J26; 330; early retirement; mortality; premature death; health behavior; endogeneity; instrumental variable; Flexible Altersgrenze; Sterblichkeit; Arbeiter; Instrumentalvariablen-Schätzmethode; Schätzung; Österreich